Environmental diagnosis of sources in the Piauí River Basin, Alagoas, Brazil - Silva, Telliane Santos Salgueiro; Brito, Pedro Lucas Cosmo de; Santos, Cícero Gomes dos; Magalhães, Ivomberg Dourado; Souza, Rafaela Barbosa de; Almeida, Camila Alexandre Cavalcante de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
It is notorious the concern with the water supply in the world, since this is a finite resource. The lack of rain, mainly in the Northeast region, allied with the environmental degradation of our water courses, has been contributing even more to the worsening of this crisis. Therefore, the objective of this work was to identify the tributaries of the Piauí River in Alagoas in the middle and lower portions of its watershed, performing its georeferencing and then a macroscopic analysis of each source. The diagnosis was made in the months of August, September and October of 2015, a survey of all the springs of this hydrographic region was carried out and they were qualified according to their degree of preservation. In order to carry out this qualification, on-site visits were carried out at these sources and, by completing a form, together with the sum of the points, it was possible to classify the degree of preservation of each source. The environmental report shows a worrisome situation from the macroscopic point of view, since none of the springs diagnosed was classified as having an excellent degree of preservation, and more than 70% of them were classified as poorly preserved.